GAMBARAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI TAMAN KANAK-KANAK KECAMATAN BANGKINANG KABUPATEN KAMPAR PROPINSI RIAU - Febrialismanto Febrialismanto. (Jurnal Pesona Dasar, 2017)
The research aims at finding out the description of rough motor of a child at 4-5 years of age at a kindergarten at Bangkinang District, Kampar Regency, Riau Province. Eight indicators are used here to monitor the description of rough motor of a 4-5 year-old child.The highest from all of the indicators is making use of playing tools outside classroom, whichaccounts for 85.17% includes in the criterion of developing very well. For the lowest indicator,there are two criteria. The first is throwing something accuratelyand making anticipatory movement that accounts for 64.83% includesin the criterion of developing as expected. Overall, rough motor ability of a 4-5 year-old at Bangkinang District kindergarten,Kampar Regency, Riau Province has 72.78% that falls into the criterion of developing as expected.